Kualitas Minyak Goreng Habis Pakai Ditinjau dari Bilangan Peroksida, Bilangan Asam dan Kadar Air - Suroso, Asri Sulistijowati (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2013)
There are habits to reuse cooking oil that for main reason of cost saving. Reusing cooking oil might be problem for health.This research aimed to study the number of peroxide number, acid value, free fatty acid, and water content of light and dark brown reused cooking oil. The quality of oil were compared to The National Standard of Indonesia (SNI 01-3741-2002) Edible Oil Quality. Peroxide number was determined by iodometric methods, free fatty acid level and acid value by alkali titration (KOH/NaOH), and water content by gravimetric methods. The oil sample were light and dark brown reused cooking oil and new packaged oil. The oil that, use as standard reference, was new packaged oil. Each oil was analyzed three times. Reuse cooking oil was got from food vendor in Bogor. The results showed that the mean of peroxide number, acid value, free fatty acid level and water content of the black colour of reused cooking oil were 7.89 O2/100g; 1.46 mg KOH/g; 0.64% and 0.61% w/w respectively. The brown colour oil were 5.15 O2/100g; 0.94 mg KOH/g; 0.41% and 0.79% w/w respectively. These light and dark brown reused cooking oils did not comply with SNI 01-3741-2002, therefore they are not suitable to be used for cooking.